The black box of governmental learning : the learning spiral : a concept to organize learning in governments - Blindenbacher, Raoul; Nashat, Bidjan; World Bank. (Washington, D.C. : International Bank for Reconstruction and Development/World Bank, 2010)
The book introduces the learning spiral - a new concept for organising effective learning events for government in the 21st century. It helps governments to learn from each other. This theory- based concept has been applied successfully over the past decade in numerous conferences, training and e-learning events all over the world. The book is directed toward practitioners in government such as members of cabinets, parliaments and courts , civil servants and politicians; civil society organisations; and international organisations. It will help them understand the challenges of learning in governemnts and offers a concept for organising effective learning events.
Includes bibliographical references.
opc 21/05/13, ijb 21/02/2019
Loans
Keywords: Public administration; Organizational learning; Active learning; Government executives